The Food Security Model in Facing Covid-19 Impact through the Reinforcement of Communal Agriculture - Rasminto Rasminto; Mihyal Ain (Program Studi Manajemen Lingkungan, 2021)
The increasing number of cases of the spread and transmission of COVID-19 to various countries in the world requires prevention and control efforts. Food security is one of the priority sectors that needs to be addressed as soon as possible, because food is the most basic need of mankind, especially in the midst of a pandemic situation, that's why food security is required to continue to explore in order to find models for strengthening food that are suitable and can produce high productivity. Based on this, this study aims to provide information about the food security model in dealing with the impact of the COVID-19 pandemic through the communal agriculture model in Indonesian agriculture. The data collection method used in this study is a literature study. The conclusion that can be drawn from this study is that the communal farming model has bright prospects in supporting the Indonesian agricultural sector during the COVID-19 pandemic because this model allows for strengthening from within the agricultural sector.